Study on the effects of mooring system stiffness on air gap response. (1st November 2021) - Li, Xu; Wei, Handi; Xiao, Longfei; Cheng, Zhengshun; Liu, Mingyue
Abstract: Air gap is a critical design consideration for semi-submersible platform. Wave slamming will easily occur for the platform with a small air gap, resulting in serious damage to the platform and endangering the safety of personnel. Current studies on the air gap response paid little attention to the effects of the mooring system on the air gap response. In this study, the effects of the mooring system stiffness on the air gap response under extreme sea conditions were studied based on a numerical model validated by experimental results. The mooring system was simplified into a combined horizontal and vertical mooring system to investigate the influence of the horizontal and vertical stiffness of the mooring system on air gap response, respectively. Gumbel distribution was used to predict the extreme air gap response owing to the randomness of disturbing waves. As the horizontal stiffness of mooring system increases, the air gap increases unstably before decreasing. When the maximal vertical stiffness of mooring system exceeds 4.5% of the heave restoring coefficient of platform, the influence of vertical stiffness cannot be negligible. Based on the results, methods for choosing optimal parameters of the catenary mooring system for maximal air gap features are proposed. Highlights: The effects of stiffness of mooring system on air gap response are presented. The accuracy of the numerical model is validated by experimental results. Methods for choosing optimal stiffness of the mooring system for maximal air gap features are proposed.